Optically transparent wideband circularly polarized antenna for 5G communication systems - Eknath C. Patil; Shashikant D. Lokhande (Discover Electronics)
Abstract This paper presents the design of an optically transparent circularly polarized antenna utilizing Indium Tin Oxide-coated Polyethylene Terephthalate (ITO-PET) as the transparent conductive material and Soda-lime glass (SLG) as the substrate. The antenna is engineered to operate within the 3.3 GHz band, supporting 5G communications, and exhibits circular polarization across the entire frequency range. The antenna demonstrates optimal boresight radiation with a peak realized gain of -0.6 dBi. Circular polarization is achieved through the incorporation of two square slots into a reference circular patch antenna, which are strategically positioned to guide surface currents in orthogonal directions, producing uniform circular polarization. Further, the Axial Ratio (AR) bandwidth is enhanced by 5.5 times from 60 MHz to 330 MHz using two square defects to the ground plane placed exactly below the slots placed to the circular patch. The Axial Ratio (AR) remains below -3 dB, covering the frequency spectrum from 3110 MHz to 3440 MHz with center frequency at 3270 MHz Experimental results from the fabricated prototype show strong correlation with simulation data, validating the proposed design.